Sunscreen Use among a Population of Saudi University Students - Mohammed I. AlJasser; Abdullah Aljumah; Mohannad Alzaydi; Abdullah Alassaf; Suliman Alassafi; Maha T. Alassafi; Mohammed Almedlej; Emad Masuadi (Dermatology Research and Practice)
Introduction. Sunscreen is an important method of sun protection. Many studies were conducted worldwide on the use of sunscreen but only few done in Saudi Arabia. The aim of our study is to assess the prevalence, practices, and factors associated with sunscreen use among Saudi university students. Materials and Methods. A cross-sectional study was performed at King Saud bin Abdulaziz University for Health Sciences in Riyadh, Saudi Arabia. A questionnaire on the use of sunscreen was created in English. Quota sampling technique was used since the sample was divided according to gender and college year. Results. A total of 1,011 students were enrolled. Approximately half were males (n = 510). Half of the students used sunscreen (n = 515, 51%). Female gender, high family income, previous history of sunburn, tanning bed use, and use of other sun protection methods were factors independently associated with sunscreen use. The main reasons for using sunscreen were prevention of sunburns, dark spots, skin cancer, and overall skin darkening. Eighty percent of participants used other methods of sun protection. Sunscreen with a sun protection factor (SPF) > 30 was used in 59% of students. However, the majority did not know if the sunscreen they use provided broad-spectrum coverage or not. Only 35% of students apply sunscreen in both sunny and cloudy days. Most students apply sunscreen less than 10 minutes before going out and do not repeat the application throughout the day. More than 90% of students seem to apply insufficient amount of sunscreen. Conclusion. Almost half of the population in the study use sunscreen. We have identified several areas of improper use of sunscreen. Increasing the awareness of effective sunscreen use in our community might be needed.